Respuesta :
1]
4*6+5*7+6*8+.....+4n(4n+2)=4(4n+1)(8n+7)/6
If we choose n=1, then 4*6=24 but 4(4*1+1)(8*1+7)/6=50. This implies that the general trm for the pattern shown is wrong. It should have been (n+3)(n+5) and not 4n(4n+2).
2] 12+42+72+.......+(3n-2)2=n(6n²-3n-1)/2
Let's set n=1, this means that 12=12.
But n(6n²-3n-1)/2
=1(6*1²-3*1-1)/2
=(6-3-1)/2
=2/2
=1
This shows that the general term is incorrect. It should have been (30n-18) which when simplified we get 6(5n-3). Even if we get to correct the left hand side the sequence will still not be equal to what's on the right given n=1.
3] 2+4+6+....+2n=n(n+1)
P(1):2=1(1+1)
P(m):2+4+6+..+2m=m(m+1)
P(m+1):2(k+1)=(k+1)(k+2)
4*6+5*7+6*8+.....+4n(4n+2)=4(4n+1)(8n+7)/6
If we choose n=1, then 4*6=24 but 4(4*1+1)(8*1+7)/6=50. This implies that the general trm for the pattern shown is wrong. It should have been (n+3)(n+5) and not 4n(4n+2).
2] 12+42+72+.......+(3n-2)2=n(6n²-3n-1)/2
Let's set n=1, this means that 12=12.
But n(6n²-3n-1)/2
=1(6*1²-3*1-1)/2
=(6-3-1)/2
=2/2
=1
This shows that the general term is incorrect. It should have been (30n-18) which when simplified we get 6(5n-3). Even if we get to correct the left hand side the sequence will still not be equal to what's on the right given n=1.
3] 2+4+6+....+2n=n(n+1)
P(1):2=1(1+1)
P(m):2+4+6+..+2m=m(m+1)
P(m+1):2(k+1)=(k+1)(k+2)